2012
DOI: 10.1111/j.1654-1103.2012.01414.x
|View full text |Cite
|
Sign up to set email alerts
|

The importance of plant life form on spatial associations along a subtropical coastal dune gradient

Abstract: Questions Does the spatial association between isolated adult trees and understorey plants change along a gradient of sand dunes? Does this association depend on the life form of the understorey plant? Location Coastal sand dunes, southeast Brazil. Methods We recorded the occurrence of understorey plant species in 100 paired 0.25 m2 plots under adult trees and in adjacent treeless sites along an environmental gradient from beach to inland. Occurrence probabilities were modelled as a function of the fixed varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 49 publications
(92 reference statements)
1
32
1
3
Order By: Relevance
“…We did not observe discernable effects of stress gradients on the organization of forest understory communities in this coastal system. Likewise, Castanho et al (2012) found no evidence that spatial life form associations change with increasing distance from seashore. Our study showed that the findings for sand dunes (Castanho et al 2012) and shrub vegetation (Pimentel et al 2007) also apply to the forest formations in the restinga.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…We did not observe discernable effects of stress gradients on the organization of forest understory communities in this coastal system. Likewise, Castanho et al (2012) found no evidence that spatial life form associations change with increasing distance from seashore. Our study showed that the findings for sand dunes (Castanho et al 2012) and shrub vegetation (Pimentel et al 2007) also apply to the forest formations in the restinga.…”
Section: Discussionmentioning
confidence: 64%
“…It seems that the restinga forest and the beach vegetation ) are capable to buffer the effects of wind and salt spray. Distance from seashore did not affect spatial associations and nurse effects in restingas (Castanho et al 2012;Castanho & Prado 2014). Moreover, in open shrub formations of the restinga, distance from seashore was not associated with floristic composition or structural parameters of the vegetation.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations